La comunicación responsable y su influencia en el comportamiento cultural de los jóvenes de la Cooperativa Baldramina alta del cantón Quevedo - Ñúñez Zambrano, Karla Gabriela (2017)
This research work has as main objective to analyze responsible communication and its influence on the cultural behavior of the young people of the Baldramina Alta cooperative of Quevedo canton in the year 2017. This study allowed to identify and to understand the causes by which the two variables to studying are united. In order to carry out this work, two types of research were used: the field and the explanatory, in order to carry out a more detailed analysis of the problem; the methods used were deductive and inductive, and among the techniques used were observation and the survey, which were applied to young people of the Baldramina Alta Cooperative. Being a large population had to apply a formula to establish the size of the study samp le, which was of 278 young people, with which the respective questionnaire of the survey was carried out, to obtain the necessary data for the elaboration of the tables and the statistical graphs, which gave the pertinent information to arrive at the necessary conclusions of this investigation. The use of the respective methods and other factors that are used to perform an investigative work, allowed to establish a relationship between the variables to be investigated and studied, thus being able to verify the hypothesis that had been proposed. Concluding that the implementation and development of a training plan on responsible journalism would be of great help to the youth of the Baldramina Alta cooperative, to improve their way of communicating and their cultural behavior.